Discourse Analysis of Religious Moderation in Digital Islamic Prophecy Content of Islamic Boarding School - Ida Kusumawati; Siti Khofsah; Unzilah Khomairotusshiyamah; Muhammad Kholilurrohman; Muhammad Thoiful Abrar; Zackyl Musthofa; Badrul Mudarris (Universitas Nurul Jadid, 2025)
Digital media is growing capable of pushing Islamic boarding schools to jump into conveying preaching through digital media content through an official Islamic boarding school account. In this context, this moderation of religious moment This become issue important How For guard balance in a diverse society. Research this approach is qualitative with method analysis related discourse with context, social, cognitive, and social as well as aspect text or Language. Data from study This in the form of content digital preaching through account official Islamic boarding school Lirboyo, Islamic boarding school Sidogiri and Islamic boarding schools red bean curd with in the form of documentation techniques. Research results this to expose discourse moderation religious constructed with the use of contextual, persuasive, and simple language related to everyday life. In addition, the digital content preaching also conveys the existence of adaptation to characteristics social so that the core message is conveyed easy for understood and acceptance. So that can conclude that the existence of digital Islamic boarding schools plays a strategic and practical role in conveying the moderation of religion in the digital era.